2020
DOI: 10.1111/aor.13741
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of skin autofluorescence, a marker of tissue advanced glycation end‐products in the fistula and non‐fistula arms of patients treated by hemodialysis

Abstract: Advanced glycosylation end‐products (AGEs) are reported to be a risk factor for cardiovascular mortality in hemodialysis (HD) patients. As serum AGEs can change with dialysis, measurement of AGEs deposited in the skin by autofluorescence (SAF) is now a recognized method of measuring AGEs. An arteriovenous fistula (AVF) is the preferred way to access blood in HD patients, and as the creation of an AVF changes blood flow distribution in the arm, we wished to determine whether this affected SAF deposition in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In almost all studies, the arm that was used to check on SAF levels and the skin color of subjects were not reported. Only two studies demonstrated that the SAF was lower in the arteriovenous fistula arm 51 . It is unclear whether this reflects a difference in the blood supply.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In almost all studies, the arm that was used to check on SAF levels and the skin color of subjects were not reported. Only two studies demonstrated that the SAF was lower in the arteriovenous fistula arm 51 . It is unclear whether this reflects a difference in the blood supply.…”
Section: Methodsmentioning
confidence: 99%
“…Only two studies demonstrated that the SAF was lower in the arteriovenous fistula arm. 51 It is unclear whether this reflects a difference in the blood supply. The value of measuring SAF in subjects with highly pigmented skin is also unclear.…”
Section: Methodsmentioning
confidence: 99%
“…After each measurement the arm was repositioned to within 1 cm of the original placement. In brief, the AGE reader illuminates approximately 4 cm 2 of the skin surface with an emission ultraviolet fluorescence light wave-length between 420 and 600 nm, which causes excitation of AGEs deposited in subcutaneous tissues, and then measures the autofluorescence-reflected light from the skin, wave length of 300-420 nm with a spectrometer [17,18]. The AGE reader has a guard to prevent external light contamination [17,18].…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the AGE reader illuminates approximately 4 cm 2 of the skin surface with an emission ultraviolet fluorescence light wave-length between 420 and 600 nm, which causes excitation of AGEs deposited in subcutaneous tissues, and then measures the autofluorescence-reflected light from the skin, wave length of 300-420 nm with a spectrometer [17,18]. The AGE reader has a guard to prevent external light contamination [17,18]. The AGE reader was fitted with an additional light source for those with darker skin pigmentation, and measurements were adjusted for skin colour by proprietary software (DiagnOptics, Groningen, Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Com isso, fatores pró-inflamatórios e seus receptores, incluindo AGEs e RAGE passam a ser expressos e acumulados em maior quantidade, resultando no aumento de AGEs-Os níveis de AGEs-sAF em pacientes submetidos a HD variam entre os estudos, possivelmente devido aos critérios de inclusão, as características das diálises utilizadas, como por exemplo, hemodiafiltração ou HD convencional, o tempo em diálise e até mesmo o tipo de acesso venoso utilizado. [140][141][142][143] Já no caso da DP, J. Jing et al, evidenciou que a carga de glicose utilizada no banho parece contribuir para o aumento de AGEs no organismo, entretanto, apesar de não termos quantificado a carga glicêmica prescrita, podemos observar pacientes submetidos a DP são mais sujeitos a acúmulo de AGEs-sAF, evidenciado após modelo de regressão linear não ajustado e ajustado 143.…”
unclassified